2014
DOI: 10.1002/ijc.28788
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of phospho‐Akt in patients with non‐small cell lung carcinoma: A meta‐analysis

Abstract: Previous studies have been inconsistent with respect to the reported associations between phospho-Akt (p-Akt) overexpression and lung cancer prognosis. In this study, we conducted a systematic review and meta-analysis to assess the prognostic value of p-Akt in patients with non-small cell lung carcinoma (NSCLC). Relevant articles were identified by searching MEDLINE. Hazard risks (HRs) from individual studies were calculated and pooled by using a random-effect model, and heterogeneity and publication bias anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…However, it could not cause any significant reduction in cell viability and pAkt levels when combined with radiation (compared to radiation alone group). Lowering of pAkt level by VCN-2 is important as pAkt is directly correlated to the poor prognosis of NSCLC [60]. Our results corroborated the earlier report since we also observed that VCN-2, alone and in combination with radiation, lowered the levels of Akt (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…However, it could not cause any significant reduction in cell viability and pAkt levels when combined with radiation (compared to radiation alone group). Lowering of pAkt level by VCN-2 is important as pAkt is directly correlated to the poor prognosis of NSCLC [60]. Our results corroborated the earlier report since we also observed that VCN-2, alone and in combination with radiation, lowered the levels of Akt (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Kctd20 has been found to associate with Akt and upregulates its phosphorylation level at Thr308 . The level of phosphorylated Akt, including Thr308 and Ser473, has also been associated with adverse survival of NSCLC patients . However, there are no reports on the prognostic value of Kctd20.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, p-AKT levels were associated with adverse survival in a univariate but not a multivariate analysis. The sample could be the limiting factor as p-AKT levels have been previously shown to be associated with survival in NSCLC; however, the results are not consistent [25,27,30]. …”
Section: Discussionmentioning
confidence: 55%
“…Several groups have investigated the activation of the PI3K pathway in NSCLC by focusing on levels of p-AKT as a marker of pathway activation. Results were obtained using immunohistochemical techniques in the majority of cases [25,26,27,28], while the prognostic role of p-AKT overexpression still remains unclear [29,30]. Immunohistochemistry techniques studying phosphoproteins are challenging to quantify accurately, while de-phosphorylation may occur ex vivo before fixation due to the instability of phosphoepitopes [31].…”
Section: Introductionmentioning
confidence: 99%